2022
DOI: 10.1111/cobi.14012
|View full text |Cite
|
Sign up to set email alerts
|

Savviness of prey to introduced predators

Abstract: The prey naivety hypothesis posits that prey are vulnerable to introduced predators because many generations in slow gradual coevolution are needed for appropriate avoidance responses to develop. It predicts that prey will be more responsive to native than introduced predators and less responsive to introduced predators that differ substantially from native predators and from those newly established. To test these predictions, we conducted a global meta-analysis of studies that measured the wariness responses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 74 publications
0
8
0
Order By: Relevance
“…Our study sites were distinct from papers in the dataset, in that we focused exclusively on desert landscapes where predators were protected. We filtered the dataset of Wallach et al (2022) to include only predation risk experiments where a Vulpes species was the predator. Including our field data, this left us with a final dataset of 19 studies comprising 80 experiments.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study sites were distinct from papers in the dataset, in that we focused exclusively on desert landscapes where predators were protected. We filtered the dataset of Wallach et al (2022) to include only predation risk experiments where a Vulpes species was the predator. Including our field data, this left us with a final dataset of 19 studies comprising 80 experiments.…”
Section: Methodsmentioning
confidence: 99%
“…We conducted a meta-analysis including our results from our field study, to test the generality of our findings. We used the data on fox studies included in the meta-analysis by Wallach et al (2022), which explores the determinants of predator recognition in prey globally. This database was comparable to our field study because it was focused on small mammals ( < 2 kg), included only experiments conducted under free-ranging conditions sympatric with foxes, and on small mammals that had been born locally.…”
Section: Meta-analysismentioning
confidence: 99%
See 1 more Smart Citation
“…For the most part, conservation has set aside these paradoxes (but see 14 ) due to claims that introduced organisms have fundamentally different—and unwanted—effects relative to native ones ( 15 , 16 ). While we acknowledge that in specific cases (especially on islands) introduced organisms have contributed to extinctions, meta-analyses have repeatedly shown that it is impossible to distinguish between native and introduced organisms on the basis of their effects ( 1721 ); that some ‘invasive’ organisms targeted for eradication turn out to be native endemic species ( 22 ); that introduced organisms are not a leading cause of biodiversity loss ( 23 ); and that when we look we find that many introduced organisms sustain ecosystem services and facilitate other species ( 2428 ). While there remains disagreement about these points among conservation scientists, we cannot ignore the fact that continued exclusion and eradication of introduced populations may exacerbate extinction of vulnerable groups of plants and animals at a time of monumental planetary change.…”
Section: Introductionmentioning
confidence: 99%
“…Mammalian alien predators are a particularly damaging group, having been implicated in the extinction of at least 87 birds, 45 mammals, and 10 reptile species worldwide (Doherty et al, 2016). As a result of evolutionary isolation, islands have a disproportionate share of global terrestrial biodiversity (Russell & Kueffer, 2019), with species often exhibiting "ecological naïveté"-that is, loss of defensive traits and behaviors needed to deal with novel predators (Carthey & Banks, 2014;Wallach et al, 2022)-making them particularly vulnerable to predation (Azumi et al, 2021;Courchamp et al, 2003;McCreless et al, 2016;Nogales et al, 2006). Although predation is often the most visible impact, invasive mammalian predators can also impact native biodiversity by competition, disease transmission, and through a wide range of cascading ecological impacts (Bourgeois et al, 2004;Carrete et al, 2022;Nogales et al, 1996;Rando et al, 2020).…”
Section: Introductionmentioning
confidence: 99%